MOLES3: Implementing an ISO standards driven data catalogue - Graham A Parton; Steven Donegan; Stephen Pascoe; Ag Stephens; Spiros Ventouras; Bryan N Lawrence (International Journal of Digital Curation, 2015)
ISO19156 Observations and Measurements (O&M) provides a standardised framework for organising information about the collection of information about the environment.Â  Here we describe the implementation of a specialisation of O&M for environmental data, the Metadata Objects for Linking Environmental Sciences (MOLES3).